1996
DOI: 10.1016/s0165-5728(96)00043-4
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment of experimental autoimmune encephalomyelitis in the Lewis rat results in loss of Vβ8.2+ and myelin basic protein-reactive cells from the spinal cord, with increased total T-cell apoptosis but reduced apoptosis of Vβ8.2+ cells

Abstract: We have studied the effects of corticosteroid treatment on the numbers of lymphocytes obtained from the spinal cords of Lewis rats with acute experimental autoimmune encephalomyelitis (EAE) induced by inoculation with myelin basic protein (MBP) and adjuvants. Flow cytometric studies showed that treatment with dexamethasone (4 mg/kg) 8-12 h prior to study on day 14 after inoculation resulted in a reduction in the numbers of CD5 + , TCR + and V 8.2 + cells in the spinal cord. Limiting dilution analysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…51,52 Additionally, in studies of experimental autoimmune encephalomyelitis (EAE), a well-established rodent model of multiple sclerosis (MS), dexamethasone treatment induced apoptosis and inhibited the CNS migration of peripheral, bystander T cells with limited impact on CNS-resident, antigen-specific T cells. 35,53 Taken together, these data suggest there may be variability of corticosteroid’s influence on CNS-resident vs. peripheral T cells, and the current study’s findings demonstrate that anti-PD-1-mediated immune responses against intracranial tumors may potentially go undeterred in the setting of corticosteroids. Corticosteroid use did not correlate with the density of infiltrating T cells in a large cohort of patients with brain metastases.…”
Section: Discussionmentioning
confidence: 50%
“…51,52 Additionally, in studies of experimental autoimmune encephalomyelitis (EAE), a well-established rodent model of multiple sclerosis (MS), dexamethasone treatment induced apoptosis and inhibited the CNS migration of peripheral, bystander T cells with limited impact on CNS-resident, antigen-specific T cells. 35,53 Taken together, these data suggest there may be variability of corticosteroid’s influence on CNS-resident vs. peripheral T cells, and the current study’s findings demonstrate that anti-PD-1-mediated immune responses against intracranial tumors may potentially go undeterred in the setting of corticosteroids. Corticosteroid use did not correlate with the density of infiltrating T cells in a large cohort of patients with brain metastases.…”
Section: Discussionmentioning
confidence: 50%
“…The cells were isolated from the spinal cords of anaesthetized rats perfused with ice-cold saline, as previously described (McCombe et al, 1996b). The spinal cord was removed by insufflation, weighed, and a single cell suspension in ice-cold RPMI 1640 containing 1% fetal calf serum (FCS) was prepared by passage through a 200 size mesh stainless steel sieve.…”
Section: Extraction Of Cells From Spinal Cordmentioning
confidence: 99%
“…The cells were labelled for flow cytometric analysis using our previously described methods (McCombe et al, 1996b). Aliquots of 10 5 -10 6 cells were washed with a 1:1 solution of serum in phosphate-buffered saline (PBS) containing 1% fetal calf serum and 0.1% sodium azide, then incubated with primary antibodies in PBS/azide for 30 min at 4°C.…”
Section: Labelling Of Cells and Flow Cytometric Analysismentioning
confidence: 99%
“…Limiting dilution analysis further revealed that the number of autoantigen-specific T cells was also decreased. 32 Notably, the numbers of apoptotic cells in the spinal cords of treated animals were increased compared with those observed in animals treated with saline. 32 This finding was consistent with the work of Pender et al, 33 who had previously demonstrated that cell apoptosis may be a major physiological mechanism of cell removal in acute EAE brain lesions.…”
Section: Glucocorticosteroids In Animal Models Of Msmentioning
confidence: 92%
“…The earliest evidence that CS may have beneficial effects in inflammatory CNS disorders was provided by Levine et al, 31 who demonstrated that therapeutic adrenalectomy enhanced the clinical signs of EAE. McCombe et al 32 showed that a single dose of dexamethasone (4 mg/kg) at disease onset resulted in a significant reduction in the numbers of T lymphocytes infiltrating into the spinal cord. Limiting dilution analysis further revealed that the number of autoantigen-specific T cells was also decreased.…”
Section: Glucocorticosteroids In Animal Models Of Msmentioning
confidence: 99%